Development of the new pedagogical skills in the context of European integration - Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Dolska, O. O.; Trynyak, M. V.; Nesterenko, Olena; Нестеренко, Олена Миколаївна; Нестеренко, Елена Николаевна; Korostylov, H. L. (My University, 2021)
The processes of globalization and informatization have a great impact on Ukrainian higher education system. In this regard, the problems of European integration of national higher education in the field of international standards occur. This article is aimed at developing a conceptual model of scientific and educational process and pedagogical skills of higher education teachers based on European integration. The necessity of using the innovative approach and the need to improve the capacity of universities to implement research and development technologies at the national level were emphasized. Innovative model of development of pedagogical skills of higher education teachers based on European integration was formed. Criteria for assessing the level of motivational and value component of pedagogical skills of the teacher were identified. The advantages and disadvantages of the development strategy of Ukrainian universities in the context of the needs of European integration of scientific and educational space were defined. It was concluded that the participation of teachers in promising research and competitions will ensure a steady increase in public funding for research in universities. The national higher education of Ukraine should be an open dynamic system.
Keywords: educational technologies; higher education management; level of motivation; national higher education